Hypospadias and the Use of the Ages and Stages Questionnaire to Evaluate Neurodevelopmental Status of Boys with Hypospadias - Cakmak, Murat; Gollu, Gulnur; Ates, Ufuk; Ergun, Ergun; Khanmammadov, Ferid; Sozduyar, Sumeyye; Telli, Onur; Kose, Kenan; Dilsiz, Habibe; Cakmak, Aytul; Kapci, Emine G.; Kucuker, Sevgi; Oner, Ozgur; Bingol-Kologlu, Meltem; Yagmurlu, Aydin; Uslu, Rana I. (European Journal of Pediatric Surgery, 2021)
Introduction Placental insufficiency is one of the reasons for the reduction of hormone production. Thus, if one of the suspected causes of hypospadias is placental insufficiency, then the neurodevelopmental status of boys with hypospadias may be impaired. The aim of this study was to evaluate the neurodevelopmental status of boys with hypospadias and guide the parents of those who need support to related departments for early intervention.Materials and Methods Boys were divided into two groups, those with hypospadias (group H) and healthy children undergoing traditional circumcision (group C). The parents of the boys completed the Ages and Stages Questionnaire (ASQ) and ASQ–Social Emotional (SE), both of which are screening instruments for the early identification of developmental and social–emotional problems, respectively.Results Seventy-eight boys had hypospadias and 59 were admitted for traditional circumcision. The group H had statistically significant more impaired scores than group C in communication, gross motor, and personal–social skill sections. The multivariate logistic regression analysis revealed that hypospadias was the independent predictive factor for communication and personal–social skills.Conclusion Hypospadias and neurologic impairment may share common etiologic factors. Accordingly, physicians should keep in mind that if a boy presents with hypospadias, the possibility of having neurologic impairment is higher than normal population and early intervention has crucial importance. Every boy with hypospadias should be evaluated for neurodevelopmental status.
Keywords: child behavior; child development; etiology; hypospadias